PROSPECTS FOR IMPROVING AND DEVELOPING ONLINE BANKING SERVICES IN COMMERCIAL BANKS OF THE REPUBLIC OF UZBEKISTAN - Ismoilov Mirshokh Valijon ugli (American Journals, 2025)
The article examines the prospects for improving and developing online banking services in commercial banks of the Republic of Uzbekistan, their remote services while maintaining reliability.
Keywords: Online banking, remote service, security, money transfers, transformation, technologies.